On error bounds for Milne's formula in conformable fractional operators - Budak, Hüseyin (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 517.9Milne's formula is a mathematical expression used to approximate the value of a definite integral. The formula is particularly useful for problems encountered in physics, engineering, and various other scientific disciplines. We establish an equality for conformable fractional integrals.  With the help of this equality, we obtain error bounds for one of the open Newton–Cotes formulas, namely, Milne's formula for the case of differentiable convex functions within the framework of fractional and classical calculus. Furthermore, we provide our results by using special cases of the obtained theorems.